Efficiency of Mathematics Courses on Enhancing of Mathematical Processes for Students in the College of Sciences in Al Imam Muhammad Ibin Saud Islamic University - Ahmed Mohamed Ragaie Elrefaie (University of Science and Technology, Yemen, 2016)
Abstract                                                                          The current research aimed at determining the efficacy of mathematics Calculus 1 (Math101), Calculus 2 (Math102), and Calculus 3 (Math203), courses in improving the mathematical processes, according to the National Council of Teachers of Mathematics (NCTM) standards. The study was prepared two tools to achieve its objectives, The first was analytical instrument for mathematics processes, which consisted of 18 elements about standards of mathematics processes (problem solving, reasoning and proof, communication, connection, representation) based on  the document of the National Council of Teachers of Mathematics (NCTM, 2000), The second was a mathematics processes questionnaire for faculty members. The findings showed that the standards of mathematical processes were available in the medium levels. The researcher recommended checking the standards of mathematical process cyclically in course of mathematics at all educational stages and suggested some of further researches.